Die feinen Unterschiede. Kultur, Kunst und Konsum im antiken Rom - Stein-Hölkeskamp, Elke (Münchner Vorlesungen zu Antiken Welten, 2020)
In studies of the Roman elite, scholars have focused on their intensive and restricted commitment to political and military achievement. This book critically considers the lasting exclusivity of this way of life, widening the scope of inquiry to demonstrate how the aristocratic environment also integrated literary pursuits, artistic production and pervasive luxury consumption.